# Simplify: `(sqrt(5/4)*sqrt(27/4))/(sqrt (3/4)*1)`

### 2 Answers | Add Yours

The expression `(sqrt(5/4)*sqrt(27/4))/(sqrt (3/4)*1)` has to be simplified.

`(sqrt(5/4)*sqrt(27/4))/(sqrt (3/4)*1)`

= `(sqrt(5*27)/sqrt(4*4))/sqrt (3/4)`

= `(sqrt(5*27)*sqrt(4/3))/sqrt(4*4)`

= `sqrt((5*27*4)/3)/4`

= `sqrt(5*9*4)/4`

= `(3*sqrt 5)/2`

**The expression **`(sqrt(5/4)*sqrt(27/4))/(sqrt (3/4)*1) = (3*sqrt 5)/2`

`(sqrt(5/4) sqrt(27/4))/(sqrt(3/4)xx1)=` `sqrt(5/4 xx 27/4 xx4/3 xx1)=` `sqrt(45/4)=sqrt( 5 xx 3^2 /2^2)=` `3/2 sqrt(5)`